Developing confidence in mental health students to recognise and manage physical health problems using a learning intervention. (July 2016) - Chadwick, Angelina Lilja; Withnell, Neil
Abstract: Globally, there is increased recognition of a higher prevalence of physical ill health and mortality in individuals with mental health problems. A review of the literature highlighted the need to address deterioration in physical health of those with mental health problems through better recognition and management on the part of mental health nurses. However, mental health nurses have been found to lack confidence and be unsure of their role within this area. The aim of the project was to develop pre-registration mental health students' confidence to be able to recognise and manage physical health deterioration through the use of high fidelity human patient simulation, the development of contextualised clinical scenarios and additional theory around the A to E mnemonic structured assessment. The project involved 95 third year mental health student nurses, using a self-rating pre and post intervention questionnaire to measure their perceived confidence levels and to evaluate the effectiveness of the learning intervention. Findings demonstrate improved overall confidence levels in recognising and managing physical health deterioration in human patient simulators displaying mental health problems. Highlights: A project to develop student mental health nurses confidence. To be able to recognise and manage physical health deterioration. The learning intervention consisted of high fidelity human patient simulation. Contextualised clinical scenarios and theory development were utilised. Project evaluation was favourable in using experiential learning methods.